2016
DOI: 10.1080/19371918.2016.1188748
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Disability Level, Leisure Satisfaction, and Quality of Life in Disabled Employees

Abstract: The purpose of this study is to investigate the disability level, leisure satisfaction, and quality of life in employees who were disabled. Six hundred twenty-seven employees who were disabled were included in this study and classified according to age, gender and disability level. In quality of life, there was significant difference between genders and age groups (p < .05). There was no significant difference neither in leisure satisfaction nor in disability level between groups (p > .05). In disability asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The majority of the PwD co-workers agreed (83.4%) that, in general, there is good communication with the PwD. These results are in line with those of Kitis et al (2017) who concluded that the employee with intellectual disabilities is seen as communicative, sociable, honest, sincere, and punctual at work. The co-workers of the PwD disagreed that the PwD usually have problems in relationships with colleagues.…”
Section: Interpersonal Communicationsupporting
confidence: 83%
“…The majority of the PwD co-workers agreed (83.4%) that, in general, there is good communication with the PwD. These results are in line with those of Kitis et al (2017) who concluded that the employee with intellectual disabilities is seen as communicative, sociable, honest, sincere, and punctual at work. The co-workers of the PwD disagreed that the PwD usually have problems in relationships with colleagues.…”
Section: Interpersonal Communicationsupporting
confidence: 83%
“…The results could indicate that a social lock-in effect, expressed by a reduction of PA for "family", and also for leisure, occurs over time due to a decrease in PA partly provided by family members. Since nonwork rather than paid employment is the norm for persons with disabilities, leisure takes on great significance for a meaningful existence and plays a vital role in habilitation or rehabilitation processes [2,23,24]. It can, however, not be ruled out that the result was due to impaired abilities associated with ageing and disability.…”
Section: A Decline In Pa For An Active Life By Social Interaction Andmentioning
confidence: 99%